Manganese-based lithium ion sieve based on electrolytic manganese anode slime and preparation method of manganese-based lithium ion sieve
Manganese-based lithium ion sieve is prepared by electrolytic manganese anode mud, which solves the problems of high energy consumption and poor adsorption performance in the prior art, and achieves efficient lithium ion adsorption and lithium resource recovery.
Patent Information
- Application Number
- CN202510010724.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing preparation methods of manganese-based lithium ion sieve have problems such as high energy consumption, long reaction time, uneven contact of raw materials and incomplete reaction, resulting in poor adsorption performance.
The electrolytic manganese anode mud is used as raw material to prepare a manganese-based lithium ion sieve through high-temperature calcination reduction, leaching of acetic acid or acetate solution, insulation reaction, high-temperature calcination and acid leaching, etc., to remove heavy metal impurities and dopant modified metal elements.
It improves the adsorption capacity, ion selectivity and recycling stability of manganese-based lithium ion sieve, reduces the risk of environmental pollution by solid waste, and promotes the recycling and utilization of lithium resources.
Smart Images

Figure CN119750651A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of manganese-based lithium ion sieves, and in particular to a manganese-based lithium ion sieve based on electrolytic manganese anode mud and a preparation method thereof. Background Art
[0002] Lithium has a wide range of uses and a rich variety of lithium resources. Brine-type lithium resources account for about 65-66% of the total lithium reserves. However, due to the rapid growth in demand for lithium resources, there will be a serious shortage of lithium resources. Therefore, the exploration and utilization of unconventional lithium resources including geothermal brine, seawater and gas field produced water has become imperative. The methods for extracting lithium from liquid lithium resources include traditional evaporation precipitation, solvent extraction, adsorption, electrochemical method, membrane separation and reaction coupled separation. Among them, the adsorption method has attracted much attention due to its significant advantages of high lithium selectivity, simple and efficient operation, high cost-effectiveness and minimal environmental impact.
[0003] Commonly used adsorbents in the adsorption method include aluminum-based adsorbents, titanium-based adsorbents, and manganese-based adsorbents. Among them, the theoretical adsorption capacity of aluminum-based adsorbents is significantly lower than that of titanium-based and manganese-based adsorbents; although titanium-based adsorbents have higher adsorption capacity, they also have obvious disadvantages, including high cost and long adsorption time; therefore, manganese-based adsorbents have received more and more attention in this field.
[0004] In manganese-based adsorbents, Li 1.6 Mn 1.6 O4 manganese-based lithium ion sieve adsorbent has the largest adsorption capacity and good anti-dissolution performance. The current preparation method usually uses chemical raw materials as synthetic raw materials. The current preparation method has problems such as high energy consumption, long reaction time, uneven raw material contact and incomplete reaction. In order to obtain better adsorption performance, the adsorbent will be doped or coated for modification. The existing modification method basically adds a modification process on the basis of synthesis, so it has defects such as high energy consumption, long synthesis cycle and high cost. Summary of the invention
[0005] In view of the above problems, the present invention aims to provide a manganese-based lithium ion sieve based on electrolytic manganese anode mud and a preparation method thereof.
[0006] The technical solution of the present invention is as follows:
[0007] On the one hand, a method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud is provided, comprising the following steps:
[0008] S1: obtaining electrolytic manganese anode mud, and performing high-temperature roasting and reduction on the electrolytic manganese anode mud, and grinding to obtain a mixture powder of Mn2O3;
[0009] S2: mixing acetic acid or acetate solution with the Mn2O3 mixture powder 1, leaching under constant temperature stirring, filtering and drying to obtain the Mn2O3 mixture powder 2;
[0010] S3: Using LiOH·H2O as a lithium source, the second Mn2O3 mixture powder as a manganese source, and ethanol as a solvent, the mixture is evenly mixed and sealed, and a heat-insulated reaction is performed, and the product obtained by the reaction is filtered, washed, and dried to obtain E-LiMnO2;
[0011] S4: calcining the E-LiMnO2 at high temperature to obtain the precursor product E-Li 1.6 Mn 1.6 O4;
[0012] S5: the precursor product E-Li 1.6 Mn 1.6 O4 is acid leached, and then the acid leaching product is filtered, washed and dried to obtain manganese-based lithium ion sieve EH 1.6 Mn 1.6 O4.
[0013] Preferably, in step S1, the high temperature calcination reduction is performed at a temperature of 750-900°C and a time of 10-90 minutes.
[0014] Preferably, in step S2, the concentration of the acetic acid or acetate solution is 1.5-4 mol / L, and the liquid-to-solid ratio during mixing is 8-12 mL:1 g; the temperature of the constant temperature stirring leaching is 70-90° C., the time is 10-60 min, and the stirring rate is 250-500 rpm.
[0015] Preferably, in step S3, the mass ratio of the lithium source to the manganese source is 2-8:1, and the volume fraction of the ethanol is 20-80%.
[0016] Preferably, in step S3, the temperature for the insulation reaction is 140-180° C. and the time is 12-24 hours.
[0017] Preferably, in step S4, the high temperature calcination is performed at a temperature of 410-450° C. and a time of 4-8 hours.
[0018] Preferably, in step S4, when high-temperature calcination is performed, the temperature is increased to the target high-temperature calcination temperature at a heating rate of 6°C / min.
[0019] Preferably, in step S5, hydrochloric acid is used for acid leaching.
[0020] Preferably, the concentration of the hydrochloric acid is 0.2-0.6 mol / L, and the hydrochloric acid reacts with the precursor product E-Li 1.6 Mn1.6 The ratio of O4 is 200-500mL:1g, and the acid leaching time is 12-36h.
[0021] On the other hand, a manganese-based lithium ion sieve based on electrolytic manganese anode mud is also provided, which is prepared by using any of the above-mentioned methods for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud.
[0022] The beneficial effects of the present invention are:
[0023] The invention uses electrolytic manganese anode mud as raw material, removes heavy metal impurities therein by roasting and leaching pretreatment means to obtain high-purity Mn2O3 doped with modified metal elements such as Fe, Al, Pb, etc., and then uses LiOH·H2O as lithium source and ethanol as solvent through heat preservation reaction, high-temperature calcination, and acid leaching to prepare a manganese-based lithium ion sieve with large adsorption capacity, good ion selectivity and good cyclic regeneration stability. The invention is not only conducive to the recycling of hazardous solid wastes, but also contributes to the development of lithium resource recovery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 Schematic diagram of the process products of Example 2 and Comparative Example 1; wherein, Figure 1 (a) and Figure 1 (c) Transmission electron microscopy (TEM) images of LMO and E-LMO, respectively; Figure 1 (b) and Figure 1 (d) Selected area electron diffraction (SAED) images of LMO and E-LMO, respectively. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0027] In one aspect, the present invention provides a method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud, comprising the following steps:
[0028] S1: Obtain electrolytic manganese anode mud, and perform high-temperature roasting and reduction on the electrolytic manganese anode mud, and grind it to obtain a mixture powder of Mn2O3.
[0029] In a specific embodiment, the temperature for high temperature calcination reduction is 750-900° C., and the time is 10-90 min. Optionally, when performing high temperature calcination reduction, the temperature is increased to the target high temperature calcination reduction temperature at a heating rate of 5° C. / min.
[0030] S2: Mixing acetic acid or acetate solution with the Mn2O3 mixture powder 1, leaching under constant temperature stirring, filtering and drying to obtain the Mn2O3 mixture powder 2.
[0031] In a specific embodiment, the concentration of the acetic acid or acetate solution is 1.5-4 mol / L, the liquid-solid ratio during mixing is 8-12 mL:1 g, the temperature of the constant temperature stirring leaching is 70-90° C., the time is 10-60 min, and the stirring rate is 250-500 rpm. Optionally, the acetate is ammonium acetate or sodium acetate.
[0032] S3: LiOH·H2O is used as a lithium source, the Mn2O3 mixture powder is used as a manganese source, and ethanol is used as a solvent. After being mixed evenly, the mixture is sealed and subjected to heat preservation reaction. The product obtained by the reaction is filtered, washed, and dried to obtain E-LiMnO2.
[0033] In a specific embodiment, the mass ratio of the lithium source to the manganese source is 2-8:1, the volume fraction of the ethanol is 20-80%, and the temperature for the insulation reaction is 140-180°C and the time is 12-24h.
[0034] In the above embodiments, the present invention uses ethanol as a solvent, which can reduce the reaction temperature and is more evenly mixed than aqueous solution raw materials at the same temperature, thereby achieving a higher product purity.
[0035] S4: calcining the E-LiMnO2 at high temperature to obtain the precursor product E-Li 1.6 Mn 1.6 O4.
[0036] In a specific embodiment, the high temperature calcination is performed at a temperature of 410-450° C. and a time of 4-8 hours. Optionally, during the high temperature calcination, the temperature is increased to the target high temperature calcination temperature at a heating rate of 6° C. / min.
[0037] S5: the precursor product E-Li 1.6Mn 1.6 O4 is acid leached, and then the acid leaching product is filtered, washed and dried to obtain manganese-based lithium ion sieve EH 1.6 Mn 1.6 O4.
[0038] In a specific embodiment, hydrochloric acid is used for acid leaching, and the concentration of the hydrochloric acid is 0.2-0.6 mol / L. The hydrochloric acid reacts with the precursor product E-Li 1.6 Mn 1.6 The ratio of O4 is 200-500mL:1g, and the acid leaching time is 12-36h.
[0039] It should be noted that acid leaching is mainly used to activate the precursor product to obtain the ion sieve. In addition to the preferred hydrochloric acid in this embodiment, acid solutions such as sulfuric acid and nitric acid in the prior art can also be applied to the present invention.
[0040] In the present invention, electrolytic manganese anode mud is used as raw material, which is solid waste generated during the electrolysis of manganese anode chamber, contains more than 40% heavy metal components, including Mn, Pb, Se, etc., and also contains trace elements such as Pb, Fe and Al. In the preparation process of the preparation method of the present invention, it can be conditionally doped into the manganese-based lithium ion sieve to change the crystal dominant surface and increase the adsorption specific surface area, thereby enhancing the adsorption performance of the manganese-based lithium ion sieve for lithium. The manganese-based lithium ion sieve prepared by the preparation method of the present invention has large adsorption capacity, good ion selectivity and good recycling stability, and helps to reduce the pollution risk of solid waste to the environment.
[0041] On the other hand, the present invention also provides a manganese-based lithium ion sieve based on electrolytic manganese anode mud, which is prepared by using any of the above-mentioned methods for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud.
[0042] Example 1
[0043] A manganese-based lithium ion sieve based on electrolytic manganese anode mud is prepared by the following steps:
[0044] (1) obtaining electrolytic manganese anode mud, placing the electrolytic manganese anode mud in a muffle furnace, heating the temperature to 900° C. at a heating rate of 5° C. / min, calcining and reducing the electrolytic manganese anode mud at 900° C. for 30 min, and grinding to obtain a mixture powder of Mn2O3;
[0045] In this embodiment, the electrolytic manganese anode mud is provided by a company in Guangxi. The main chemical components and contents of the electrolytic manganese anode mud are shown in Table 1:
[0046] Table 1 Main chemical composition and content of electrolytic manganese anode mud (wt%)
[0047] Element Mn Pb S Fe Al As Cu Content 68.6036 7.2893 0.6025 0.1983 0.1974 0.076 0.0154
[0048] (2) mixing a 2 mol / L ammonium acetate solution with the Mn2O3 mixture powder 1 at a solid-liquid ratio of 10:1, leaching in a water bath at 80°C for 10 min with constant stirring, with the stirring speed always maintained at 300 rpm, filtering and drying to obtain a Mn2O3 mixture powder 2;
[0049] (3) Using LiOH·H2O as the lithium source (8 g), the Mn2O3 mixture powder as the manganese source (4 g), and ethanol as the solvent (the volume fraction of ethanol is 28.57%), the mixture is mixed evenly and then transferred to a sealed hydrothermal reactor;
[0050] (4) placing the hydrothermal reactor in an oven at 160° C. for 24 hours of heat preservation reaction, filtering, washing, and drying the product obtained by the reaction to obtain E-LiMnO2;
[0051] (5) placing the E-LiMnO2 in a muffle furnace, heating the temperature to 410°C at a heating rate of 6°C / min, and calcining at 410°C for 4 hours to obtain the precursor product E-Li 1.6 Mn 1.6 O4 (denoted as E-LMO);
[0052] (6) the precursor product E-Li 1.6 Mn 1.6 O4 is acid-leached with hydrochloric acid, the concentration of which is 0.5 mol / L. The hydrochloric acid reacts with the precursor product E-Li 1.6 Mn 1.6 The ratio of O4 is 200mL:1g, the acid leaching time is 24h, and then the acid leaching product is filtered, washed and dried to obtain manganese-based lithium ion sieve EH 1.6 Mn 1.6 O4 (denoted as E-HMO).
[0053] Example 2
[0054] Different from Example 1, in step (3) of this example, the ratio of lithium source to manganese source is 4:1, that is, the amount of LiOH·H2O used is 8 g, and the amount of the second mixed powder of Mn2O3 used is 2 g.
[0055] Example 3
[0056] Different from Example 1, in step (3) of this example, the ratio of lithium source to manganese source is 6:1, that is, the amount of LiOH·H2O used is 8 g, and the amount of the second mixed powder of Mn2O3 used is 1.33 g.
[0057] Example 4
[0058] Different from Example 1, the ratio of lithium source to manganese source in step (3) of this example is 8:1, that is, the amount of LiOH·H2O used is 8 g, and the amount of the second mixed powder of Mn2O3 used is 1 g.
[0059] Example 5
[0060] Different from Example 2, the temperature in step (4) of this example is 180°C.
[0061] Comparative Example 1
[0062] A manganese-based lithium ion sieve is prepared by the following steps:
[0063] (1) LiOH·H2O was used as a lithium source (8 g), commercially available Mn2O3 powder was used as a manganese source (2 g), and ethanol was used as a solvent (the volume fraction of ethanol was 28.57%). The mixture was evenly mixed and then transferred to a sealed hydrothermal reactor;
[0064] (2) placing the hydrothermal reactor in an oven at 160° C. for 24 hours of heat preservation reaction, filtering, washing, and drying the product obtained by the reaction to obtain LiMnO2;
[0065] (3) placing the LiMnO2 in a muffle furnace, heating the temperature to 410°C at a heating rate of 6°C / min, and calcining the LiMnO2 at 410°C for 4 hours to obtain a precursor product Li 1.6 Mn 1.6 O4 (denoted as LMO);
[0066] (4) the precursor product Li 1.6 Mn 1.6 O4 is acid-leached with hydrochloric acid, the concentration of which is 0.5 mol / L. The hydrochloric acid reacts with the precursor product E-Li 1.6 Mn 1.6 The ratio of O4 is 200mL:1g, the acid leaching time is 24h, and then the acid leaching product is filtered, washed and dried to obtain manganese-based lithium ion sieve H 1.6 Mn 1.6 O4 (denoted as HMO).
[0067] Comparative Example 2
[0068] Different from Example 2, the temperature in step (4) of this example is 140°C.
[0069] Comparative Example 3
[0070] Different from Example 2, the solvent in step (3) of this example is deionized water.
[0071] Comparative Example 4
[0072] Different from Example 5, the solvent in step (3) of this example is deionized water.
[0073] Since the preparation method of the present invention uses electrolytic manganese anode mud as raw material, which is a hazardous solid waste, the leaching toxicity of the synthetic product needs to be considered. The toxicity of the manganese-based lithium ion sieve of the present invention is tested using the "Solid Waste Leaching Toxicity Leaching Method Sulfuric Acid and Nitric Acid Method" HJ / T299-2007, and the results show that no lead ions are leached in the solution. According to the national standard "Hazardous Waste Identification Standard Leaching Toxicity Identification" GB 5085.3-2007, the present invention has no risk of leaching heavy metals to pollute the environment.
[0074] The manganese-based lithium ion sieves prepared in each embodiment and each comparative example were subjected to Li + Adsorption performance test: Specifically, a certain amount of LiOH·H2O was weighed and dissolved in deionized water to prepare Li + The concentration of the simulated brine was 450.54 mg / L (pH = 12.4). At 20 ° C, the manganese-based lithium ion sieve was added as an adsorbent at a dosage of 5 g / L, and adsorbed for 24 hours. After the adsorption, the adsorbed mixed solution was filtered through a 0.45 μm microporous filter membrane, and the Li in the filtrate was determined by flame atomic absorption spectrometry. + concentration, and calculate the adsorbent to Li according to the following formula + Adsorption capacity:
[0075]
[0076] Where: Q e is the adsorption capacity, mg / g; C0 is the initial lithium ion concentration, mg / L; C e is the lithium ion concentration after adsorption, mg / L; V is the solution volume, L; m is the mass of the ion sieve, g.
[0077] Li + The adsorption performance test results are shown in Table 2:
[0078] Table 2Li + Adsorption performance test results
[0079] Example Adsorption capacity (mg / g) Comparative Example Adsorption capacity (mg / g) Example 1 35.22 Comparative Example 1 30.54 Example 2 40.86 Comparative Example 2 30.12 Example 3 40.25 Comparative Example 3 28.14 Example 4 40.59 Comparative Example 4 32.55 Example 5 39.88 - -
[0080] As can be seen from Table 2, compared with Example 2, the adsorption capacity of the manganese-based lithium ion sieve prepared by using commercially available pure Mn2O3 powder as the manganese source is not as high as the adsorption capacity of the manganese-based lithium ion sieve prepared by using electrolytic manganese anode mud as the raw material of the present invention. The manganese-based lithium ion sieve of the present invention is modified by doping with elements such as Fe, Al, and Pb contained in electrolytic manganese anode mud, and the adsorption capacity is increased by 33.79% compared with the manganese-based lithium ion sieve prepared by using commercially available pure Mn2O3 powder as the manganese source, and the adsorption performance is significantly improved.
[0081] By comparing Example 2 of the present invention and Comparative Example 2, it can be seen that when the temperature for the heat preservation reaction is insufficient, the adsorption energy absorption of the product will be reduced.
[0082] By comparing Example 2 of the present invention with Comparative Example 3 and Example 5 of the present invention with Comparative Example 4, it can be seen that the product obtained by using ethanol as a solvent has higher adsorption performance than that obtained by using deionized water as a solvent. This is because the chemical properties of ethanol reduce the reaction temperature, and the raw materials of the comparative aqueous solution are mixed more evenly at the same temperature, thereby making the product purity higher. However, using deionized water as a solvent will lead to incomplete synthesis reaction, resulting in lower purity of the adsorbent product, and therefore the adsorption capacity of the obtained product is lower.
[0083] In addition, the adsorption specific surface area of the manganese-based lithium ion sieve of Example 2 and Comparative Example 1 was tested, wherein the electron microscope image and electron diffraction image before acid leaching activation were as follows: Figure 1 As shown (the surface of the material is observed by electron microscope, and the change of the crystal plane advantage is observed by electron diffraction), after activation (when using the present invention, E-LMO is activated to obtain E-HMO and then put into use, and it is usually stored in the form of E-LMO) the test results are shown in Table 3:
[0084] Table 3 Adsorption specific surface area of manganese-based lithium ion sieve in Example 2 and Comparative Example 1
[0085]
[0086] from Figure 1 As can be seen from Table 3, the use of electrolytic manganese anode mud to prepare Fe, Al, Pb and other doped manganese-based lithium ion sieves is beneficial to change the (111) and (100) crystal plane advantages, and the specific surface area of E-HMO is 64.0082m 2 / g compared with the specific surface area of HMO 89.4981m 2 / g increased by 39.82%, thereby increasing more adsorption sites.
[0087] In addition, the manganese-based lithium ion sieve of the present invention was tested for lithium ion selectivity. Real gas field produced water from a gas field in Sichuan was selected as the lithium extraction solution. The adsorbent was mixed with the real gas field produced water at a dosage of 5 g / L of adsorbent at 20°C and adsorbed for 24 hours. After the adsorption, the adsorbed mixed solution was filtered through a 0.45 μm microporous filter membrane, and the Li in the filtrate was determined by flame atomic absorption spectrometry. + 、Na + , K + , Ca 2+ Mg 2+ concentration, and calculate the adsorbent to Li according to formula (1). + 、Na + , K + , Ca 2+ Mg 2+ The adsorption capacity of the ion is then calculated according to the following formula: d To judge the selectivity:
[0088]
[0089] The water quality indicators of the real gas field produced water in this test example are shown in Table 4, and the calculation results of the adsorption capacity and distribution coefficient of the manganese-based lithium ion sieve in Example 2 are shown in Table 5:
[0090] Table 4 Water quality indicators of real gas field produced water
[0091] index pH <![CDATA[Li + (mg / L)]]> <![CDATA[Na + (mg / L)]]> <![CDATA[K + (mg / L)]]> <![CDATA[Ca 2+ (mg / L)]]> <![CDATA[Mg 2+ (mg / L)]]> Numeric 7.25 158.39 28491.93 2026.26 3121.52 311.03
[0092] Table 5 Calculation results of adsorption capacity and distribution coefficient
[0093] ion Adsorption capacity (mg / g) Partition coefficient <![CDATA[Li + ]]> 17.01 231.93 <![CDATA[Na + ]]> 31.05 1.09 <![CDATA[K + ]]> 1.26 0.62 <![CDATA[Ca 2+ ]]> 1.04 0.33 <![CDATA[Mg 2+ ]]> 0.22 0.72
[0094] It can be seen from Table 5 that the manganese-based lithium ion sieve of the present invention satisfies the selectivity of Li + >K + >Na + >Mg 2+ , for Li + It showed good adsorption selectivity.
[0095] The manganese-based lithium ion sieve of the present invention was subjected to a cycle performance test, specifically repeating the above adsorption behavior 7 times, and calculating the lithium ion adsorption capacity and manganese dissolution rate of each cycle, wherein the test results of Example 2 are shown in Table 6:
[0096] Table 6 Cyclic performance test results
[0097] Cycle times Adsorption capacity (mg / g) Cycle times Adsorption capacity (mg / g) 1 17.01 5 16.75 2 17.25 6 16.82 3 16.83 7 16.53 4 16.99 - -
[0098] It can be seen from Table 6 that the manganese-based lithium ion sieve of the present invention has excellent cyclability in real water samples, and the adsorption capacity is only reduced by 2.9% after 7 cycles, which can be ignored.
[0099] In summary, the present invention can utilize Fe, Al, Pb and other elements in electrolytic manganese anode mud to dope and modify the manganese-based lithium ion sieve to improve its adsorption performance. Compared with the prior art, the present invention has significant progress.
[0100] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical content to make some changes or modifications to the embodiment is an equivalent embodiment of the present invention. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud, characterized in that: The following steps are involved: S1: obtaining electrolytic manganese anode mud, and performing high-temperature roasting and reduction on the electrolytic manganese anode mud, and grinding to obtain a mixture powder of Mn2O3; S2: mixing acetic acid or acetate solution with the Mn2O3 mixture powder 1, leaching under constant temperature stirring, filtering and drying to obtain the Mn2O3 mixture powder 2; S3: Using LiOH·H2O as a lithium source, the second Mn2O3 mixture powder as a manganese source, and ethanol as a solvent, the mixture is evenly mixed and sealed, and a heat-insulated reaction is performed, and the product obtained by the reaction is filtered, washed, and dried to obtain E-LiMnO2; S4: calcining the E-LiMnO2 at high temperature to obtain the precursor product E-Li 1.6 Mn 1.6 O4; S5: the precursor product E-Li 1.6 Mn 1.6 O4 is acid leached, and then the acid leaching product is filtered, washed and dried to obtain manganese-based lithium ion sieve EH 1.6 Mn 1.6 O4.
2. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 1, characterized in that: In step S1, the high temperature calcination reduction is performed at a temperature of 750-900°C and a time of 10-90 minutes.
3. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 1, characterized in that: In step S2, the concentration of the acetic acid or acetate solution is 1.5-4 mol / L, and the liquid-to-solid ratio during mixing is 8-12 mL:1 g; the temperature of the constant temperature stirring leaching is 70-90° C., the time is 10-60 min, and the stirring rate is 250-500 rpm.
4. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 1, characterized in that: In step S3, the mass ratio of the lithium source to the manganese source is 2-8:1, and the volume fraction of the ethanol is 20-80%.
5. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 1, characterized in that: In step S3, the temperature for the heat preservation reaction is 140-180° C. and the time is 12-24 hours.
6. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 1, characterized in that: In step S4, the high temperature calcination is performed at a temperature of 410-450° C. and a time of 4-8 hours.
7. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 6, characterized in that: In step S4, when high-temperature calcination is performed, the temperature is increased to the target high-temperature calcination temperature at a heating rate of 6°C / min.
8. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 1, characterized in that: In step S5, hydrochloric acid is used for acid leaching.
9. The method for preparing a manganese-based lithium ion sieve based on electrolytic manganese anode mud according to claim 8, characterized in that: The concentration of the hydrochloric acid is 0.2-0.6 mol / L, and the hydrochloric acid reacts with the precursor product E-Li 1.6 Mn 1.6 The ratio of O4 is 200-500mL:1g, and the acid leaching time is 12-36h.
10. A manganese-based lithium ion sieve based on electrolytic manganese anode mud, characterized in that: The manganese-based lithium ion sieve is prepared by the method for preparing the manganese-based lithium ion sieve based on electrolytic manganese anode mud as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Manganese series lithium ion sieve adsorbent and preparation method of precursor thereof
CN101961634A
Purification process of manganese anode slime
CN105695751A
Method for preparing lithium ion sieve from lithium manganate battery waste, and prepared lithium ion sieve
CN108199104A
Spherical manganese-based lithium ionic sieve and preparation method thereof
CN110451570A
Preparation method of columnar manganese lithium ion sieve compound
CN112591798A